Новий етап археологічного освоєння курганів енеоліту—бронзи Південно-Східної Європи - Шилов, Ю.О. (Археологія, 1992)
Розглядаючи розвиток вивчення степових курганів України та інших територій, автор наголошує на його перспективності у справі історизації археології. В дискуссионной форме излагается историография освоения курганов, которая — по мнению автора — переживает ныне IV этап, начатый исследованием в 1972—1981 гг. курганов у с. Староселье Великоалександровского р-на Херсонской области. До этого были пройдены: I — вещеведческий этап (пополнения, прежде всего, музейных коллекций); II — культуроведческий этап (начатый в первые годы XX в. исследованиями В. А. Городцова в Харьковской губ.); III — архитектуроведческий этап (заявленный докладом М. П. Грязнова в 1960 г.). На этих этапах были освоены, в основном, различные категории инвентаря, погребения, курганные насыпи. IV — этап синтеза трех предыдущих, начало освоения кургана как целостного источника.
Освоение заключается, главным образом, в расшифровке мифотворчества строителей курганов. Последующее сопоставление этих мифов с исторически засвидетельствованными (записанными) способно существенно историзировать археологию Юго-Восточной Европы, углубить ее историю с киммерийского (конец II тыс. до н. э.) до начала арийского времени (средина III — средина IV тыс. до н. э.).
В заключение выдвигается ряд гипотез, порожденных началом IV этапа освоения курганов и конкретизирующих основное направление вышеуказанной историзации. The paper presents a disputable view of the author concerning historiography of the study of barrows which endures now the 4th stage beginning with the study of barrows near vil. Staroselie, Velikoaleksandrovsky district, Kherson Region (1972—1981). The preceding stages were as follows: the 1st stage, the study of things (replenisment of museum collections); the 2nd stage, the study of culture (it was initiated early in the 20th cent, by V. A Gorodtsov in the Kharkov province); the 3d stage, the study of architecture (it was claimed by the report made by M. P. Gryaznov in 1960). Those three stage were devoted, mainly, to the study of various categories of tools, burials, burial mounds. The 4th stage is a synthesis of three previous stages, an onset of the study of a barrow as an integral source.
The study consists mainly in interpretation of myth-creation of the barrow builders. The following comparison of those myths with historically witnessed (recorded) data is able to historize essentially archaeology of South-Eastern Europe, to make an insight into its history from the Cimmerian (end of the 2nd millennium В. C.) to the Aryan age (mid of the 3d — mid of the 4th millennia В. C.).
Some hypotheses are put forward as engendered by the onset of the 4th stage of the study of barrows and concretizing a basic trend of the above mentioned historization.